The Influence of Profitability, Leverage, and Firm Size on Firm Value with Dividend Policy as a Mediating Variable - Fitriya, Novi Rahma; Ernawati, Sri; Syahdan, Saifhul Anuar; Syam, Akhmad Yafiz (Asosiasi Dosen Akuntansi Indonesia, 2025)
This study aims to analyse the effect of profitability, leverage, and firm size on firm value mediated by dividend policy. This study uses a purposive sampling method. This study includes non-cyclical industries on the Indonesia Stock Exchange for the period 2020-2023, with a population of 23 companies and a sample size of 125. The data were analysed and hypotheses tested using the Structural Equation Modelling Partial Least Squares (SEM-PLS). The findings of this study indicate that profitability, leverage and firm size have positive influences on firm value. Dividend policy has a significant direct effect on firm value. However, the indirect effect of independent variables through dividend policy was not significant.